Prevalence and distribution of livestock schistosomiasis and fascioliasis in Côte d’Ivoire: results from a cross-sectional survey - Jules N. Kouadio; Jennifer Giovanoli Evack; Louise Y. Achi; Dominik Fritsche; Mamadou Ouattara; Kigbafori D. Silué; Bassirou Bonfoh; Jan Hattendorf; Jürg Utzinger; Jakob Zinsstag; Oliver Balmer; Eliézer K. N’Goran (BMC Veterinary Research, 2020)
Abstract Background Schistosoma and Fasciola are zoonotic parasites of public health and veterinary importance. However, while the epidemiology of schistosomiasis in humans is well studied, little is known about fascioliasis and schistosomiasis in livestock in Côte d’Ivoire. This study aimed to determine the prevalence and the distribution of livestock schistosomiasis and fascioliasis across Côte d’Ivoire. In 2018, we conducted a cross-sectional survey in abattoirs and farms in 13 departments of Côte d’Ivoire. In abattoirs, the mesenteric veins and livers of slaughtered cattle, sheep and goats were examined for adult Schistosoma and Fasciola flukes. Faeces from live cattle, goats and sheep were collected and examined for Schistosoma and Fasciola eggs using a sedimentation technique. Results A total of 386 cattle, 174 goats and 151 sheep from abattoirs and 435 cattle, 22 goats and 176 sheep from farms were sampled. The observed prevalence of schistosomiasis was higher in slaughtered animals. Fascioliasis was more prevalent in farm animals. The prevalence of schistosomiasis in slaughtered cattle varied between 5.9% (95% confidence interval (CI): 0.7–19.7%) and 53.3% (95% CI: 37.9–68.3%) with the highest prevalence observed in Ouangolodougou in the North. Cattle from farms had a relatively low prevalence of schistosomiasis, with the highest prevalence found in Ouangolodougou (2.4%, 95% CI: 0.7–6.1%). The prevalence of fascioliasis varied considerably from one department to another, ranging from nil (95% CI: 0.0–18.5%) to 50.8% (95% CI: 43.4–58.2%), with the highest prevalence found in farm cattle in Dikodougou in the North. Sheep and goats had a lower prevalence of schistosomiasis and fascioliasis than cattle. In slaughtered animals, cattle aged 4 years and older were at highest risk for schistosomiasis (odds ratio (OR): 2.4; 95% CI: 1.0–5.6) and fascioliasis (OR: 2.1; 95% CI: 1.1–3.9). In farm animals, male cattle had higher odds of being infected with Schistosoma (OR: 4.3; 95% CI: 0.7–26.9) than females. Conclusions Our study confirms that schistosomiasis and fascioliasis are endemic in livestock across Côte d’Ivoire. A strategic control programme should be considered, especially for cattle, including providing drinking water in troughs to reduce faecal contamination of water sources by cattle.